From forgotten to frontier: vindicating Latin America’s indigenous biotechnology - Francisca Villanueva-Flores; Igor Garcia-Atutxa (Journal of Ethnobiology and Ethnomedicine)
Abstract This study provides a critical reassessment of indigenous Latin American biotechnologies, uniquely integrating ethnographic, historical, and biochemical analyses to reveal their scientific sophistication and contemporary potential. It examines ancestral practices historically overlooked or marginalized, such as microbial fermentation in traditional beverages (masato, pozol, and pulque), medicinal and nutritional uses of plant mucilages, and natural encapsulation methods using clays and plant-derived polymers. We demonstrate that these indigenous biotechnological systems represent more than ethnographic curiosities; they are early examples of empirical technologies anticipating fundamental principles now central to probiotics, encapsulation pharmacology, and sustainable agriculture. By spotlighting previously under-documented practices and emphasizing their deep cultural and ecological integration, this review fosters a more inclusive understanding of scientific knowledge. It underscores both the ethical and epistemological imperative to recognize and incorporate indigenous innovations into contemporary scientific frameworks. This novel perspective not only recovers and revalues historically marginalized knowledge but also promotes intercultural collaboration, ultimately strengthening sustainability and modern biotechnological innovation. Graphical abstract